Experimental characterization of the ITER TF structure cooling in HELIOS test facility. Issue 1 (November 2015) - Hoa, C; Rousset, B; Lacroix, B; Nicollet, S; Vallcorba, R; Bessette, D; Vostner, A; Gauthier, F
Abstract: During ITER plasma operation, large thermal loads are generated in the stainless steel Toroidal Field (TF) coil casing. To minimize the impact on the temperature of the TF Cable in Conduit Conductor (CICC), these heat loads are intercepted by case cooling channels which are implemented at the interface to the winding pack. One of the design options for the case cooling channels consists of a stainless steel pipe inserted in a rectangular groove which is machined in the casing and filled by a charged resin of high thermal conductivity. A higher number of cooling pipes is arranged at the plasma facing wall of the case, thus providing a better shielding to the TF conductor at high field. To assess the efficiency of the cooling pipes and their thermal coupling with the charged resin, experimental characterizations have been performed. First of all, the thermal resistance vs temperature of some of the individual components of a TF coil has been measured on representative samples in a cryogenic bench. Further characterizations have been performed on an integrated mock-up of the TF cooling scheme at cryogenic temperature in HELIOS test facility at CEA Grenoble. The mock-up consists of a piece of TF casing that can be heated uniformly on its surface, one cooling channel implemented in the groove which is filled with the charged resin, the filler, the ground insulation, the radial plate and one insulated CICC. The cooling pipe and the CICC are cooled by supercritical helium at 4.4 K and 5 bar; the instrumentation consists of temperature, pressure and mass flow sensors. Both stationary and transient operating modes have been investigated to assess the thermal efficiency of the case cooling design. The experimental tests are presented and the first results are discussed and analyzed in this document.